2017
DOI: 10.1002/ace.20247
|View full text |Cite
|
Sign up to set email alerts
|

Gendering Collaboration: Adult Education in Feminist Leadership

Abstract: This chapter explores the potential of feminist leadership to encourage more participatory ways of engaging and learning in this deeply troubled world. Feminist leadership includes but is not limited to collaborative leadership. Adult learning is inherent to feminist leadership insofar as leaders must strategize according to the contexts in which they find themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Numerous research studies, reviews of literature, books, and reports identified obstacles that stand in the way of women's career progression in different sectors and countries (AAUW, 2016;AIEA, 2018;Alsharif, 2018;AQU Catalunya, 2019;Arar, 2018;Bayir & Dönmez, 2020;Cheung, 2021;Clover et al, 2017;Colantuono, 2010;Coleman, 2020;Davis, 2012;Folke et al, 2020;Gaudette et al, 2018;Griffiths et al, 2018;Kim & Kim, 2020;Maheshwari & Nayak, 2020;McCullough, 2020;McKinsey, 2021;Regulska, 2021;Yousaf & Schmiede, 2017). These obstacles occur on individual, organizational, socio-cultural, economic, and systemic levels.…”
Section: Barriers For Women's Professional Advancementmentioning
confidence: 99%
“…Numerous research studies, reviews of literature, books, and reports identified obstacles that stand in the way of women's career progression in different sectors and countries (AAUW, 2016;AIEA, 2018;Alsharif, 2018;AQU Catalunya, 2019;Arar, 2018;Bayir & Dönmez, 2020;Cheung, 2021;Clover et al, 2017;Colantuono, 2010;Coleman, 2020;Davis, 2012;Folke et al, 2020;Gaudette et al, 2018;Griffiths et al, 2018;Kim & Kim, 2020;Maheshwari & Nayak, 2020;McCullough, 2020;McKinsey, 2021;Regulska, 2021;Yousaf & Schmiede, 2017). These obstacles occur on individual, organizational, socio-cultural, economic, and systemic levels.…”
Section: Barriers For Women's Professional Advancementmentioning
confidence: 99%
“…While other feminist theories often remain "stuck" on the theoretical level, FEL embraces the practical application as direct reflection in leadership practices (Blackmore, 1996). Instead of ascribing leadership traits to specific gender categories, FEL aims at trying to encapsulate how gendered leadership experiences have been shaped by a variety of -isms while at the same time striving to effect positive change (Clover et al, 2017).…”
Section: Establishment Of a Sentiment Of Caring Within The Institutio...mentioning
confidence: 99%
“…The horizontalist form of organizing seen in OL rejects hierarchies that reproduce power structures and exclude diversity (Kokkinidis, 2012). Instead, such social movements create space for a feminist leadership that is inherently focused on the nature of change that a collective group of individuals can bring through processes of social action (Clover et al, 2017). This is important for HRD professionals because developing feminist leaders would not focus on techniques or processes of performativity traditionally addressed in leadership development programs (Learmonth & Morrell, 2019).…”
Section: Practical Contributionsmentioning
confidence: 99%